Social Dimensions of Moral Responsibility - Hutchison, Katrina; Mackenzie, Catriona; Oshana, Marina (Oxford University Press, 2018)
Philosophical theorizing about moral responsibility has recently taken a "social" turn, marking a shift in focus from traditional metaphysical concerns about free will and determinism. Yet despite this social turn, the implications of structural injustice and inequalities of power for theorizing about moral responsibility remain surprisingly neglected in philosophical literature. Recent theories have attended to the interpersonal dynamics at the heart of moral responsibility practices, and the role of the moral environment in scaffolding agential capacities. However, they assume an overly idealized conception of agency and of our moral responsibility practices as reciprocal exchanges between equally empowered and situated agents. The essays in this volume systematically challenge this assumption. Leading theorists of moral responsibility, including Michael McKenna, Marina Oshana, and Manuel Vargas, consider the implications of oppression and structural inequality for their respective theories. Neil Levy urges the need to refocus our analyses of the epistemic and control conditions for moral responsibility from individual to socially extended agents. Leading theorists of relational autonomy, including Catriona Mackenzie, Natalie Stoljar, and Andrea Westlund develop new insights into the topic of moral responsibility. Other contributors bring debates about moral responsibility into dialogue with recent work in feminist philosophy, and topics such as epistemic injustice, implicit bias and blame. Collectively, the essays in this volume reorient philosophical debates about moral responsibility in important new directions.